2022
DOI: 10.1155/2022/4487864
|View full text |Cite|
|
Sign up to set email alerts
|

Long Noncoding RNA Zinc Finger Antisense 1 Affects Glucocorticoid-Induced Osteonecrosis of the Femoral Head by Performing as a ceRNA for MicroRNA-124-3p and Accelerating Transforming Growth Factor Type III Receptor

Abstract: In recent years, plentiful studies have uncovered the long noncoding RNA’s (lncRNA’s) momentous functions in osteonecrosis of the femoral head (ONFH), but the specific mechanism has not been fully illustrated. The study was to figure out lncRNA Zinc finger antisense 1 (LncZFAS1)’s biological function and its latent downstream molecular mechanism in glucocorticoid- (GC-) induced ONFH. The results manifested LncZFAS1 and transforming growth factor type III receptor (TGFBR3) were elevated, while microRNA- (miR-) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%